Analysis of voltage fluctuation impact on induction motors by an innovative equivalent circuit considering the speed changes. Issue 2 (1st January 2017) - Ghaseminezhad, Morteza; Doroudi, Aref; Hosseinian, Seyed Hossein; Jalilian, Alireza
Abstract : The most commonly used motor in industries is induction motor. This motor is exposed to various power quality disturbances. A frequent power quality disturbance which has an adverse effect on induction motor is voltage fluctuations. In this study, the behaviour of three‐phase induction motors under voltage fluctuation conditions is studied. By using the theory of dynamic phasor, an innovative equivalent circuit in which the speed fluctuations are taken into account is presented. The currents, efficiency and power factor under voltage fluctuation conditions are evaluated by the proposed equivalent circuit. The variations of these quantities due to different voltage fluctuation characteristics are also investigated. The simulation results are validated by measurements on the laboratory test setup which comprises a 1.1 kW induction motor excited by a programmable power supply unit.